PENGGUNAAN MEDIA EDUKASI BULETIN PADA TOPIK EYE MAKEUP BERBASIS ARTIFICIAL INTELLIGENCE (AI) - Hanna Nurul Husna; Amaira Utami; Ai Nurlaelasari Rusmana; Riana Nurismawati; Putra Habib Dhitareka (Jurnal Abdi Insani, 2026)
AI technology has developed rapidly. Its use in education is currently a focus of attention. The purpose of this activity is to provide education to the public about eye makeup and its impact on eye health in the form of bulletin media. The target subjects of this activity are people who receive information via Whatsapp links. The material delivered through the bulletin is facts and myths about eye makeup and health; how to choose makeup products that are safe for the eyes, and the risk of eye infection due to the use of unhygienic eye makeup. The content of the bulletin media is compiled with the help of AI, which is then evaluated and edited by the author for the accuracy of the information. The media design was carried out using Canva and image assets from Freepik. From the results of the activity, it was found that the majority of participants were not aware that the bulletin media was made by integrating AI technology. In addition, all participants, who were women, also stated that they felt the benefits of the information conveyed from the bulletin media. Thus, it can be concluded that AI can be integrated in the creation of media for community service activities while still upholding responsibility and ethics.